2003
DOI: 10.4049/jimmunol.171.11.5908
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Plasmid DNA Activates Dendritic Cells via Toll-Like Receptor 9 (TLR9) but Functions in TLR9-Deficient Mice

Abstract: We analyzed whether the immunobiology of vaccinating plasmid DNA containing a transcription unit for OVA is influenced by immunostimulatory CpG motifs in the plasmid backbone. Indeed, plasmid DNA differentially activated in vitro myeloid and plasmacytoid dendritic cells (DCs) provided they expressed the CpG-DNA receptor, Toll-like receptor 9 (TLR9). Dependent on the DC subset, activation resulted in type 1 IFN production, while both DC subsets produced IL-6 and up-regulated expression of costimulatory molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 37 publications
4
124
1
2
Order By: Relevance
“…DNA vaccination. 33,34 Considering all these studies, it can be concluded that TLR9 contribute but is dispensable for T cell responses elicited by DNA vaccines delivered, and targeting TLR9 represents an opportunity for improvement of adaptive immune responses. Indeed, strategies introducing more CpG motifs into the antigenencoding plasmid DNA vector have been shown to further boost antibody titers in i.m.…”
Section: Methodsmentioning
confidence: 99%
“…DNA vaccination. 33,34 Considering all these studies, it can be concluded that TLR9 contribute but is dispensable for T cell responses elicited by DNA vaccines delivered, and targeting TLR9 represents an opportunity for improvement of adaptive immune responses. Indeed, strategies introducing more CpG motifs into the antigenencoding plasmid DNA vector have been shown to further boost antibody titers in i.m.…”
Section: Methodsmentioning
confidence: 99%
“…Even milligram doses of plasmid may not provide a dose of CpG equivalent to that found in the synthetic CpG adjuvant. Furthermore, in one study, plasmid DNA vaccines were found to be immunogenic in both normal and TLR9 Ϫ/Ϫ mice (17). Nonetheless, increasing the total amount of plasmid administered i.m.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In vitro-generated FL-dependent DC (FL-DC) were generated and sorted essentially as described by us (24). In short, BM cells were cultured in the presence of human or murine recombinant FL for 8 -9 days.…”
Section: Cell Generation In Culture and Preparation From Lymphoid Orgmentioning
confidence: 99%